STUDIES OF SYSTEMIC AND LOCAL CYTOKINE LEVEL IN RETINAL VEIN OCCLUSION ASSOCIATED WITH ANTIANGIOGENIC THERAPY - E. A. Drozdova; D. Yu. Khokhlova; E. A. Mezentseva; K. V. Nikushkina (Медицинская иммунология, 2018)
The paper presents results of studying systemic and local level of cytokines in retinal vein occlusion following antiangiogenic therapy. The study of cytokine concentrations was conducted in the general group of patients, and depended on the type of retinal vein occlusion before and after intravitreal injections of Ranibizumab. We examined thirty-two patients with retinal vein occlusion. We performed standard ophthalmological examinations, spectral optical coherence tomography, fluorescent angiography in order to establish the type of retinal vein occlusion. We determined concentration of vascular endothelial growth factor (VEGF), endothelin-1, interleukin-1, interleukin-6 and tumor necrosis factor-α in serum and tears by enzyme immunoassay before treatment, and 3 months after regular injections of Ranibizumab. The obtained data prove that all the patients with retinal vein occlusion had significantly increased VEGF levels in blood serum and tear fluid compared to the control group. We have revealed a positive correlation between levels of VEGF in tear fluid, and interleukin-1, interleukin-6 and endothelin-1 in the tears, as well as with VEGF concentrations and endothelin-1 in serum. We have found an increase of endothelin-1 in tear and serum, alongd with interleukins and tumor necrosis factor-α in tear fluid, with maximal concentrations of some factors in ischemic type of retinal vein occlusion. Following antiangiogenic therapy in patients with non-ischemic type, there was a significant decrease in VEGF level, interleukin-6 and tumor necrosis factor-α in the serum, vascular endothelial growth factor and interleukin-1 in tears. In patients with ischemic type, a significant decrease in VEGF and interleukin-6 concentrations in tears, endothelin-1 and interleukin-1 in blood serum. Thus, our research showed the role of interleukins, tumor necrosis factor-α, vascular endothelial growth factor and endothelin-1 in pathogenesis of retinal vein occlusion.